Behavioral intervention grounded in motivational interviewing and behavioral economics shows promise with Black and English-speaking Latino persons living with HIV with unsuppressed HIV viral load in New York City: A mixed methods pilot study - Gwadz, Marya; Serrano, Samantha; Linnemayr, Sebastian; Cleland, Charles M.; Cluesman, Sabrina R.; Freeman, Robin M.; Kellam, Kinsey; De Stefano, Corey; Israel, Khadija; Pan, Emily (Frontiers in Public Health, 2022)
Introduction. Sustained HIV viral suppression is the ultimate goal of HIV treatment. African American/Black and Latino persons with HIV (PWH) in the United States are less likely than their White peers to achieve and sustain viral suppression. To address these disparities, we developed a “low-touch” behavioral intervention drawing on motivational interviewing and behavioral economics. The intervention had three main components: 1) a motivational interviewing counseling session, 2) 16 weeks of automated text messages and quiz questions about HIV management, where participants earned points by answering quiz questions, and 3) a lottery prize, based on viral suppression status, number of points earned, and chance (max. 275). Materials and methods. The intervention was tested in a pre-test/post-test design. The present pilot study used mixed methods to explore the intervention’s feasibility, acceptability, impact, and ways it could be improved. Participants engaged in a baseline assessment, qualitative interview, and two structured follow-up assessments over an 8-month period, and provided laboratory reports to document HIV viral load. We carried out descriptive quantitative analyses. Qualitative data were analyzed using a directed content analysis approach. Data integration was carried out using the joint display method. Findings. Participants (N=40) were 50 years old, on average (SD=11), and approximately half (58%) were male. Close to two-thirds (68%) were African American/Black and 32% were Latino. Participants were diagnosed with HIV 22 years ago on average (SD=8). The intervention was feasible (e.g., mean number of quiz questions answered = 13/16) and highly acceptable. While not powered to assess efficacy, the proportion with suppressed HIV viral load increased from baseline to follow-up (46% participants at the first, 52% participants at the second follow-up evidenced HIV viral suppression). In qualitative analyses, perspectives included that overall, the intervention was acceptable and useful, it was distinct from other programs, lottery prizes were interesting and appreciated but not sufficient to motivate behavior change, and the structure of lottery prizes was not sufficiently clear. Regarding data integration, qualitative data shed light on and extended quantitative results, and added richness and context. Conclusion. This low-touch intervention approach is sufficiently promising to warrant refinement and study in future research.